The Effect of Leadership on Employee Performance with Total Quality Management (TQM) as a Mediating Variable in Indonesian Petroleum Companies: A Case Study - Wagimin, Wagimin; Kusrini, Elisa; Ali, Juhary; Noor Helia, Vembri (International Journal of Integrated Engineering, 2019)
The score of employees‟ performance of a petroleum company, for the last few years’ achievement, have not yet met a significant increase. There is also a relationship between the organizational strategy, the Total Quality Management (TQM), and the organizational performance, with the mediating rules of TQM. This research is to identify and measure the level of factors that influence the effectiveness of work performance of employees who work in petroleum companies by identifying variable relationships including transformational leadership, transactional leadership, and TQM. This paper aims to determine the relationship between the variables mentioned above and the performance of employees in the oil and gas industry in Balikpapan Indonesia as samples using data from 250 employees. Analysis of the study using multivariate namely Structural Equation Modeling (SEM). The result shows that transformation leadership has positive effects on total quality management and employee performance. Second, transactional leadership has positive effects on total quality management and employee performance. Third, total quality management has positive effects on employee performance. Fourth, total quality management can mediate the indirect influence of transformational leadership on employee performance. Fifth, total quality management can mediate the indirect influence of transactional leadership on employee performance.